THE BATTLE OF CAJAMARCA: THE CIVILIZATIONAL COST OF MILITARY (MIS)EDUCATION - Stanar, Dragan (The Policy of National Security, 2025)
This paper analyses the Battle of Cajamarca as a paradigmatic example of the civilizational cost of military miseducation. Exploring the context, course, and consequences of the battle between the Spanish conquistadors led by Pizarro and the Inca, commanded by the divine ruler Atahualpa, the author argues that the victory of the drastically outnumbered Spanish force over the Inca army was not merely the result of technological and tactical superiority, but primarily a consequence of the Spanish commanders’ superior educational tradition, including military education in the broader sense. Through the analysis of advantages in weaponry, tactics, and the foundations for strategic decision-making on both sides, the author demonstrates that the Spanish conquistadors derived their advantage from a wide array of knowledge – military engineering, tactics, the social sciences, and a deep understanding of enemy culture – while the Inca, deprived of literacy and an institutionalized educational system, relied on superstition and improvisation. The author concludes that this battle must not remain a mere historical curiosity but should serve as a warning about the necessity of systematic, high-level intellectual military education in modern armed forces to prevent potential strategic catastrophes in future conflicts – catastrophes that could mark the end of a culture or even an entire civilization.